The use of tramadol at the Groote Schuur chronic pain management clinic (CPMC): a medicine usage evaluation - Muissa, Mbombo Marie Astrid (Department of Anaesthesia and Perioperative Medicine, 2026)
Background: The use of tramadol in the management of chronic pain has recently become controversial. Amidst rising reports on potential for abuse and its exclusion from latest international guidelines, the conduct of a Medicine Usage Evaluation (MUE) of the drug is relevant to inform future training and practice. Methods: A cross sectional retrospective descriptive chart review of the use of tramadol for the year 2021 was conducted at the Groote Schuur Chronic Pain Management Clinic (CPMC). A total of 104 folders were reviewed. Descriptive statistics summarise the data. Results: The average person with chronic pain who was being prescribed tramadol included in this MUE was female, receiving a disability grant and in their late fifties (57.28y ±12.32). A median of three comorbidities (IQR 4) were recorded in the folders. The median duration of clinic attendance was 10,5 years (IQR 11,5). Chronic spinal pain (61%) was the most common diagnosis. Atypical tramadol dosages were recorded. Only 4% of patients attributed improvement of their pain to tramadol therapy. Good prescription practices were adhered to for the majority of criteria, the key domains with shortcomings were in documentation of the severity of pain, documentation of assessment for potential drug interactions, and documentation of referral for non-pharmacological treatments. Conclusion: The MUE on the use of tramadol at the Groote Schuur CPMC was characterised by good prescription practices with regard to documentation on patient profile, pain diagnosis and management. We recommend the use of standardised protocols for follow up visits and moving to electronic records. The lack of improvement associated with tramadol therapy reported by patients was concerning. In such circumstances, we support the use of a patient-centred tapering strategy with atypical dosages not exceeding the maximum recommended daily dose and the integration of non-pharmacological treatments.